Linalool improve biochemical damage and fatty acids composition of testes on fasting male rats - Dayangac, Alpaslan; Bahsi, Muammer; Ozkaya, Ahmet; Yilmaz, Okkes (My University, 2011)
The aim of this study was to evaluate fatty acids compositions, oxidative stress levels and some antioksidant levels in the testes of 24 h fasted rats and linalool application. Adult male Wistar albino rats were assigned as Control (C), 24 h fasted (24 h F) group and added linalool (120 mg kg-1) during 24 h fasted (24 h F+L) groups. After applications, the animals were killed and the testes were excised for determination of tissue malondialdehyde, Glutation Peroxidase (GSH-Px), the activity of superoxide dismutase and determination of tissue fatty acids compositions. The activites of Superoxide Dismutase (SOD), Glutathione peroxidase (GSH-Px) and the level of Malondialdehyde (MDA) in testicular tissue specimens were determined spectrophotometrically. The fatty acid compositons in the testes were analyzed as percent by gas chromatography (GC). Researchers calculated between C 16:0 (palmitic acid) andC22:6 (docosahexaenoic acid) fatty acids in the testes of all experimental groups. Treatment with fasted rats resulted in a significant reduction inC16:l (palmitoleate) fatty acids when compared to the control rats (p<0.05). C16:l fatty acids were higher in linalool application than fasted groups (p<0.05). C22:4 (docosatetraenoic Acid), C22:5 (docosapentaenoic acid), C22:6 n3 (docosahexaenoic acid) fatty acids were lower in the fasted group than the control group. In addition, C22:4, C22:5, C22:6 fatty acids compositions in the linalool treatment group were higher than the fasted group (p<0.05). Saturated fatty acids levels in all experiment groups were not change as statistically (p>0.05). SOD and GSH-Px levels in the fasted rats were statistically lower than control groups (p<0.05). Both SOD and GSH-Px levels in the linalool application groups were not statistically a change compared to fasted groups (p>0.05). In addition, MDA levels in the fasted groups were higher than control groups. Besides, MDA levels in the linalool application groups were lower compared to fasted groups (p<0.05). These findings indicate that fasted state has oxidative effects on testicular tissue and linalool has protective effects on male reproductive system. © Medwell Journals, 2011.
Keywords: Fasting; Fatty acids; GSHPx; Linalool; MDA; Oxidative stress; Rat; SOD; Testes